Study of antepartum haemorrhage and its maternal and perinatal outcome - Tyagi, Priyanka; Yadav, Nidhi; Sinha, Parul; Gupta, Uma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Antepartum haemorrhage (APH) is defined as bleeding from or into the genital tract after the period of viability until delivery of fetus. Etiology includes placenta previa, abruptio placentae, local causes, systemic causes and idiopathic origin. Objective of this study was to identify factors associated with APH, and to quantitate maternal morbidity, mortality and perinatal outcome in patients with APH at a tertiary care center in India. Methods: The study was a retrospective observational study and patient information was obtained from delivery records of 100 women presenting at gestational age of 28 weeks and above with APH. All patients with bleeding per vagina after 28 weeks of gestation were included in the study and were grouped as – Placenta Previa (PP), Abruptio Placenta (AP) or unknown causes. Results: Out of total 100 cases of APH, placenta previa contributed to 80%, abruptio placenta 19% and 1% unknown causes. Overall maternal mortality was 6%. Perinatal mortality was 42%. Prevalence of low birth weight and preterm babies was high. Conclusions: APH is a major cause of maternal and perinatal morbidity and mortality which could be prevented by early registration, regular antenatal care, early detection of high risk cases, and early referral to higher center. Good facilities for caesarean section, availability of blood banks and multidisciplinary approach with a good NICU can improve maternal and perinatal outcome of APH. The results of this study were found in good agreement with previous studies.